Pengaruh Permainan Tradisional Selodor terhadap Keterampilan Interaksi Sosial Siswa di SDN 1 Mamben Daya: The Influence of the Traditional Selodor Game on Students' Social Interaction Skills at SDN 1 Mamben Daya - Syamsur Rizal (Pendidikan Al-Gafari, 2025)
Traditional games have significant potential in developing students’ social skills; however, their application in formal education remains limited. This study is motivated by the importance of social interaction skills as essential competencies for students in communication, cooperation, empathy, and conflict resolution. The traditional game selodor was selected because, in addition to its cultural value, it provides real opportunities for students to engage in meaningful interactions within an enjoyable and collaborative environment. This research employed a quantitative approach with a pretest-posttest control group design. The population consisted of 60 students from grades IV and V at SDN 1 Mamben Daya in the 2023/2024 academic year, with a purposive sample of 40 students equally divided into experimental and control groups. The research instrument was a social interaction skills questionnaire covering communication, cooperation, empathy, and conflict resolution, which had been validated and tested for reliability. Data were collected through a pretest, treatment involving six sessions of selodor, and a posttest, and then analyzed using the t-test at a 0.05 significance level. The findings revealed a significant improvement in students’ social interaction skills in the experimental group compared to the control group. These results indicate that the selodor game effectively enhances students’ abilities to build social relationships, manage differences, and actively participate in group activities.In conclusion, the study confirms that the traditional game selodor is effective as a pedagogical strategy for fostering social interaction skills among elementary school students. The implications highlight the need for teachers to integrate traditional games into classroom learning and extracurricular activities to strengthen students’ social competence and character development.